2009
DOI: 10.2135/cropsci2008.08.0462
|View full text |Cite
|
Sign up to set email alerts
|

Haploidy in Cultivated Wheats: Induction and Utility in Basic and Applied Research

Abstract: The usefulness of haploid plants in basic research in cytogenetics, genetics, evolution, and practical plant breeding is well known. Haploid plants provide an efficient research tool for studies on induced mutagenesis and genetic transformation. They also help elucidate the genetic control of chromosome pairing inherently present in allopolyploids such as bread wheat, durum wheat, and oats. Genetic control of chromosome pairing in haploid nuclei has helped in assessing intergenomic relationships. By analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 144 publications
(265 reference statements)
0
48
2
3
Order By: Relevance
“…With DH production systems established, homozygous lines can be achieved in one generation, which would allow to reduce the time and cost of cultivar development (Dunwell 2010;Ferrie and Caswell 2010;Germanà 2011). The system has been effectively used in barley, wheat (Jauhar et al 2009;Ferrie and Caswell 2010), maize (Smith et al 2008;Chang and Coe 2009), and various Brassica species (Belmonte et al 2006;Fang et al 2006;Zhang et al 2008;Takahira et al 2011;Winarto and Teixeira da Silva 2011). The genotype is one of the crucial factors evaluated in many plants (Ferrie et al 1995;Dunwell 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With DH production systems established, homozygous lines can be achieved in one generation, which would allow to reduce the time and cost of cultivar development (Dunwell 2010;Ferrie and Caswell 2010;Germanà 2011). The system has been effectively used in barley, wheat (Jauhar et al 2009;Ferrie and Caswell 2010), maize (Smith et al 2008;Chang and Coe 2009), and various Brassica species (Belmonte et al 2006;Fang et al 2006;Zhang et al 2008;Takahira et al 2011;Winarto and Teixeira da Silva 2011). The genotype is one of the crucial factors evaluated in many plants (Ferrie et al 1995;Dunwell 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ali used 223 CNN(RICL3A)s developed using the monosomic method (Law 1966;Yen & Baenziger 1992) and doubled haploidy (Lizarazu et al 1992;Jauhar et al 2009) and 32 markers to precisely map the QTLs identified by Campbell et al (2003). Phenotypic data was collected from 5 to 6 environments using four replications.…”
Section: Current Researchmentioning
confidence: 99%
“…Haploidy offers an efficient method for producing truly homozygous lines, thus accelerating plant breeding. DH-derived wheat cultivars have been released elsewhere (Jauhar et al 2009). Interspecific hybridization allows the introgression of diversity from wheat's wild relatives, thus bringing genes with large or small effects not available in the wheat cultigen pool.…”
Section: Evolution and Diversitymentioning
confidence: 99%